CONSEQUÊNCIAS SOCIOAMBIENTAIS APÓS DESCONTINUAÇÃO DO PROGRAMA BOLSA VERDE EM ASSENTAMENTOS RURAIS NO MUNICÍPIO DE INÁCIO MARTINS (PARANÁ) - NOVAK, MARICLÉIA APARECIDA LEITE (2023)
Payments for ecosystem services programs provide economic incentives for potential providers of ecosystem services to guarantee the provision or maintenance of these services. The program of payments for environmental services Bolsa Verde sought to encourage the conservation of ecosystems, promoting citizenship and better living conditions by raising the income of the most economically vulnerable populations, which were inserted in conservation units, rural settlements and traditional communities. Despite the benefits and praise for the program, it ran until December 2017, and was suspended by the Michel Temer government, with no budget line foreseen for the program since January 2018. Thus, this work sought to analyze the socio-environmental consequences resulting from the interruption of the Bolsa Verde Program (PBV) in rural settlements of agrarian reform in the municipality of Inácio Martins- Paraná. Methodologically, this study has a qualitative approach with the triangulation of three central constructs for the analysis of care with environmental services. These constructs are kinetic landscape analysis, historical analysis, and techno-economic analysis. The results showed that the Bolsa Verde Program was directly connected with the socioeconomic and socioenvironmental life of the beneficiaries, for the time it was in force. However, with its discontinuity, the adoption of practices for converting forest land into agricultural land became the rule within the Santa Rita and Evandro Francisco settlement, causing actors who wanted to remain in the communities to adhere to the practice of territorial conversion as their only option. Historical analysis demonstrates that human behavior is intensely habituated to following the actions taken by the community as a whole. The socioeconomic analysis was crucial to understanding that obtaining easy income, in volumes much higher than those paid for by the Bolsa Verde program, was the decisive point for choosing to convert the land. The landscape analysis showed that extractive practices were already very present in the three communities, however, with the inclusion of the PBV in 2011, this reality began to change and the forests began their regeneration process. However, with the discontinuity of the PBV, the acceleration of deforestation was noticed again. It should also be noted that this is an unprecedented study in the world and is associated with the need to expand knowledge about the field of ASF discontinuation.